2017
DOI: 10.1186/s12885-017-3860-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression, regulation of DEN and HBx induced HCC mice models and comparisons of tumor, para-tumor and normal tissues

Abstract: BackgroundHepatocellular carcinoma (HCC) is the leading cause of cancer mortality. Chemical and virus induction are two major risk factors, however, the potential molecular mechanisms of their differences remain elusive. In this study, to identify the similarities and differences between chemical and virus induced HCC models, we compared the gene expression profiles between DEN and HBx mice models, as well as the differences among tumor, para-tumor and normal tissues.MethodsWe sequenced both gene and microRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…may be due to heterogeneous disease backgrounds of the patients in the analyzed cohorts. In addition, a recent study on DEN‐induced hepatoma in mice showed that expression of miR‐146b‐5p is stronger in the highly inflammatory para‐tumor tissue compared to normal and tumor tissue, in line with a considerable impact of the tumor environment on the modulation of miR‐146b‐5p expression.…”
Section: Discussionmentioning
confidence: 83%
“…may be due to heterogeneous disease backgrounds of the patients in the analyzed cohorts. In addition, a recent study on DEN‐induced hepatoma in mice showed that expression of miR‐146b‐5p is stronger in the highly inflammatory para‐tumor tissue compared to normal and tumor tissue, in line with a considerable impact of the tumor environment on the modulation of miR‐146b‐5p expression.…”
Section: Discussionmentioning
confidence: 83%
“…On the contrary, both models shared common deregulated genes involved in metabolic pathways and redox processes. Moreover, early growth response 1 'Egr1', activating transcription factor 3 'Atf3' and Kruppel-like factor 4 'Klf4' resulted as the main regulatory factors in HBX mice controlling cancer-associated signaling pathways, such as PI3K/AKT, MAPK, Ras, and p53, which role in hepatocarcinogenesis is well established [59]. Notably, several oncogenes and tumor-suppressor (TS) genes deregulated in human HCC were controlled by these transcription factors, highlighting the reliability of the HBX mouse model with respect to the human pathology.…”
Section: Hbx Transgenic Mouse and Mir-224mentioning
confidence: 99%
“…Multifocal mutations can be seen even in a single tumor and tumor doubling time may vary between tumor nodules (5). It should also be noted that the tumor microenvironment has high inflammatory properties and may cause changes in tumor behavior (6). The liver, lungs, and bones are the most common sites of recurrence after LT respectively (7).…”
Section: Discussionmentioning
confidence: 99%